Comparison of Serum Brain-Derived Neurotrophic Factor Levels in Diabetic Patients With and Without Retinopathy - Rashid, Romana R (Cureus, 2020)
Introduction Diabetes mellitus (DM) is a disease of carbohydrate, protein, and fats metabolism that results in hyperglycemia. It may also result from defects in the secretion of insulin from beta cells or in its action on target cells or both. Objective To determine the levels of brain-derived neurotrophic factor (BDNF) and glycated hemoglobulin (HbA1c) with the progression of retinopathy. Methodology The study was done on 80 patients who were divided into four groups (A, B, C, D), with 20 individuals each, on the basis of their diabetic status and fundoscopic findings. Serum BDNF levels were measured by using an enzyme-linked immunosorbent assay kit (Glory Science Co., Taichung City, Taiwan). Results On analysis, a significant decline was seen in serum BDNF levels in diabetics as compared with non-diabetics (p < 0.001), but a significant reduction in levels with the progression of retinopathy was observed (p < 0.001). Statistical analysis All the data were processed using the Statistical Package for the Social Sciences (SPSS) v20.0 (IBM Corp., Armonk, NY). Conclusion There is a significant decline in serum BDNF levels in type 2 diabetics with retinopathy in comparison with the healthy control group.